Innovation Discrete Approach Based on Arabic Language Test Assessment - Pangestika, Eliana; Baroroh, R. Umi; Maknuna, Salma Lulu (Institut Agama Islam Negeri Curup, 2024)
This article aims to describe the assessment of Arabic language tests, and innovate Arabic language assessment using a discrete approach, in Arabic language books for class VII Madrasah Tsanawiyah published by Department Religion of Â Republic Indonesia. This research uses qualitative research methods with library study techniques. Primary data comes from Arabic books published by the Ministry of Religion. While secondary data comes from related documents, books and journals. This research aims to explain, 1. Various approaches to Arabic language tests. 2. Analysis of the Arabic language test approach in the Class VII Mts Arabic language textbook. 3. Assessment innovation with a discrete test approach for Class VII Mts Arabic language textbooks. The results of this research illustrate that there are five types of approaches in Arabic language tests, namely: Traditional Approach, Discrete Approach, Integrative Approach, Pragmatic Approach, Communicative Approach. Through the researcher's analysis, the majority of MTs in class VII Arabic language books use a pragmatic approach in Arabic language tests. such as conversation questions, context-based text comprehension questions, and multiple choice cloze tests. So, there is a need for innovative Arabic language tests with a discrete approach in Class VII MTs Arabic language textbooks. Overall, the discrete testing approach offers numerous benefits for both educators and students, including enhanced precision in assessment, personalized learning experiences, fairness in evaluation, and opportunities for innovation.